Electric Motor Maintenance and Troubleshooting, 2nd Edition, 2nd Edition - Hand, Augie (McGraw-Hill Education TAB, 2011)
A fully up-to-date, hands-on guide to electric motors Keep electric motors running at peak performance! Electric Motor Maintenance and Troubleshooting, Second Edition explains in detail how all types of AC and DC motors work. Essential for anyone who needs to buy, install, troubleshoot, maintain, or repair small to industrial-size electric motors, this practical guide contains new information on three-phase motors along with coverage of the latest test instruments. Drawing on his more than 40 years of experience working with electric motors, expert author Augie Hand provides a wealth of tested procedures to pinpoint and correct any kind of issue. He'll help you decide whether to replace a motor, take it offline for repair, or repair it in place--decisions that can reduce down time. End-of-chapter questions reinforce the material covered in the book. Quickly and accurately diagnose electric motor problems and find effective solutions with help from this fully updated classic. Electric Motor Maintenance and Troubleshooting, Second Edition covers: Troubleshooting and testing DC machines AC electric motor theory Single-phase motors Three-phase induction motors Troubleshooting less common motors, including synchronous, two-speed one-winding, and multispeed Test instruments and services.